2023
DOI: 10.3390/biom13010162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cannabis on Memory Consolidation, Learning and Retrieval and Its Current Legal Status in India: A Review

Abstract: Cannabis is one of the oldest crops grown, traditionally held religious attachments in various cultures for its medicinal use much before its introduction to Western medicine. Multiple preclinical and clinical investigations have explored the beneficial effects of cannabis in various neurocognitive and neurodegenerative diseases affecting the cognitive domains. Tetrahydrocannabinol (THC), the major psychoactive component, is responsible for cognition-related deficits, while cannabidiol (CBD), a non-psychoactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 229 publications
0
6
0
Order By: Relevance
“…In general, public opinion on the legalization of cannabis use is increasingly becoming favorable, 4 which may be attributed to a growing literature alluding to the potential medical benefits of cannabis without exposing people to the health risks. 14 , 22 , 23 Prior authors from India also have suggested that legalization can help curb young people from using unknown products. 6 However, research has documented the increasing use of cannabis among young people following legalization, with associated high-risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In general, public opinion on the legalization of cannabis use is increasingly becoming favorable, 4 which may be attributed to a growing literature alluding to the potential medical benefits of cannabis without exposing people to the health risks. 14 , 22 , 23 Prior authors from India also have suggested that legalization can help curb young people from using unknown products. 6 However, research has documented the increasing use of cannabis among young people following legalization, with associated high-risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis, in fact, is that the aberrant cognitive trajectories produced in the prenatal period by THC exposure could be rescued by the wide-spectrum activity of CBD. Indeed, CBD administration has been reported to improve cognitive deficits in several domains, which may vary depending on the pathological condition and/or the dosage ( Esposito et al, 2011 ; Campos et al, 2015 ; Peres et al, 2016 ; García-Baos et al, 2021 ; Meyer et al, 2021 ; Niloy et al, 2023 ). In our experimental setting, CBD administration, before the test sessions, normalized the impaired cognitive scores of the adolescent male rat offspring exposed prenatally to THC, independently from the emotional/motivational salience of the task.…”
Section: Discussionmentioning
confidence: 99%
“…CB1 receptors have a significant influence on memory and cognitive processes. They are concentrated in regions of the brain associated with memory formation and learning, such as the hippocampus [76,77]. Activation of CB1 receptors can affect memory consolidation and the ability to acquire new information.…”
Section: Endocannabinoid Receptor Type 1 (Cb1)mentioning
confidence: 99%